PENGEMBANGAN PEMBELAJARAN PAI MODEL ADDIE DI SMP INSAN CENDEKIA MENDIRI BOARDING SCHOOL, SIDOARJO - Muhammad Khairul Basyar (Universitas Muhammadiyah Prof Dr Hamka, 2020)
Education is the process of changing one's behavior through teaching and training so that they become more mature. The lack of application of PAI learning values